Tugas Dan Peran Kepala Desa Dalam Perlindungan Hukum Bagi Korban Kekerasan Dalam Rumah Tangga (Studi Kasus di Kelurahan Candimulyo Kecamatan Jombang Kabupaten Jombang) - Hafifah Islamiyah Putri; Muhammad Andri; Tri Susilowati (GLOBAL SCIENTS PUBLISHER, 2025)
This article generally discusses the concept of Domestic Violence (KDRT), narrowed down to the issue of abuse by husbands toward their wives. Problems occurring in villages are not limited to governance, customary management, and matters formally regulated under Law No. 6 of 2014, but go beyond these. Violent behavior within the household has now become a highly serious issue at the community level. The purpose of this study is to identify the duties and roles of the Village Head in providing legal protection for victims of domestic violence and to examine the legal protection afforded to victims of domestic violence. This research employs a normative juridical method with a statutory approach, which is then linked to the realities found in practice. The findings show that the role of the Head of Candimulyo Village includes providing guidance such as advice, physical and spiritual counseling, and participating as a third party in resolving issues and seeking solutions to address domestic violence. The forms of legal protection offered by the Candimulyo Village Head in dealing with domestic violence are also highlighted. The Village Head holds the authority to address social issues within the village, including Domestic Violence (KDRT), as stipulated in several regulations, such as: Law No. 6 of 2014 concerning Villages, which grants village heads the authority to administer village governance and resolve social issues; and Law No. 23 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT), which obligates public officials, including village heads, to report any known acts of domestic violence.